Uniportal video-assisted thoracoscopic surgery in a two-year-old chronic empyema patient: challenges faced in the first case from the Indian subcontinent - Dantis, Klein; Reazaul Karim, Habib Md; S. Kurwe, Mahesh; Singh, Vikramjit (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Recently, there has been a rise in thoracic empyema in the pediatric population [1]. The uniportal video-assisted thoracoscopic surgery (U-VATS) for chronic empyema in adult patients has been advantageous as it is associated with less pain, faster recovery and better cosmetic results [2]. However, the role of U-VATS in pediatric patients below 3 years old is still anecdotal and less reported to date. Likewise, one-lung ventilation (OLV) in infants and young children is not unknown, but challenging, as the advantages of respiratory mechanics while positioned in lateral decubitus, as seen in adults, are absent in this age group [3]. Although OLV is described in children for video-assisted thoracoscopic surgery (VATS), experience and reports with U-VATS are scarce. We present a case of chronic empyema with lung abscess in a 2-year-old pediatric patient managed with U-VATS under general anaesthesia employing OLV.